0699 Examining the Relationship Between Sleep and Cognitive Function In Older Adults Living With HIV. (12th April 2019) - Frain, Judith A
Abstract: Introduction: Poor sleep is recognized as a serious problem for older adults living with HIV. Research has indicated that over 75% of this population suffer from a variety of sleep problems which negatively impact health and quality of life. This pilot study examined the association between sleep and cognitive function in a sample of older adults living with HIV, where their HIV was well controlled with antiretroviral therapy. Methods: Forty adults aged 50 years and older and living with HIV were recruited for this study. Participants completed a demographic and health history form at study entry. Actigraph watches were worn for one week, with study participants also completing a sleep diary, fatigue survey and daytime sleepiness survey each day. After one week participants returned to the clinic and completed the Pittsburgh Sleep Quality Index (PSQI) and performed cognitive testing using the NIH Toolbox and the Montreal Cognitive Assessment (MoCA). Results: Results of the Pearson correlation indicated that there was a statistically significant negative relationship of moderate strength between global sleep and cognitive function (r = -.47, p = .015). In addition the relationships between cognitive function and sleep latency (r = -.43, p = .030), and cognitive function and sleep efficiency (r -.44, p = .025) were also moderate in strength and statistically significant, indicting that poorer sleep correlated with lower cognitive function. Conclusion: The study provides evidence that poor sleep negatively impacts the ability to age successfully while living with HIV. Despite well-controlled HIV virus, sleep was identified as poor for 86% of study participants, and 58% experienced mild cognitive impairment. Finding ways to improve sleep may be beneficial in improving cognitive function for this population. Since declines in cognitive function negatively impact a person's ability to manage their medications, routine assessment and treatment of sleep problems has the potential to improve medication adherence, a vital component of successfully managing HIV disease. Support (If Any): : This study was supported through a grant funded by Sigma Theta Tau International and the National Gerontological Nurses Association